Supplementation For Diarrhea Control In Hospitalized Geriatric Patients On Enteral Nutrition - Janaina Bach Naslowski Pocidoni; Magda Rosa Ramos da Cruz; Ivone Mayumi Ikeda Morimoto; Ludimilla Mendonça; Camila Werner Engelhardt; Jaqueline Naomi Fujimura (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To compare results of prebiotic, probiotic and synbiotic supplementation for the control of diarrhea in older patients receiving enteral nutritional therapy during hospitalization at a school hospital in Curitiba, state of Paraná. METHODS: The study was retrospective, by analysis of medical records corresponding to the visits performed between 2014 and 2018. RESULTS: A total of 75 patients were analyzed. The time of occurrence of diarrhea ranged from 1 to 16 days, with a mean of 2.69 days after the onset of therapy for reestablishment of the intestinal microbiota. As for the therapies introduced, 8 possible prescriptions of isolated and / or combined supplements were found as the first choice. Of the patients analyzed, 52% switched from supplementation during the occurrence of diarrhea; some using up to 5 different products. Of the 48% of patients who used a single product / combination from the beginning to the end of diarrhea, they generally started with a higher dose and decreased over time, with those starting at a lower dose having to increase it to stop diarrhea. In addition, there was statistical significance when comparing the time of diarrhea between patients who received a single product / combination and those who did supplemental exchanges throughout the treatment. CONCLUSION: Establishing a single prescription, whether of isolated or combined products and sticking to it, besides starting with a higher dose, seems more effective in controlling diarrhea in hospitalized geriatric patients, reinforcing the importance of establishing a protocol for prescription.